2021
DOI: 10.9734/jpri/2021/v33i30a31610
|View full text |Cite
|
Sign up to set email alerts
|

Study to Determine the Incidence of High HbA1c in Patients with Ischemic Stroke at Bilawal Medical College, Kotri, Sindh, Pakistan

Abstract: Aim: To study the incidence of HbA1c elevation in patients with ischemic stroke whose blood glucose levels were normal within the last six months. Study Design: A cross-sectional study. Place and Duration: This cross-sectional study of the 96 patients with cerebral ischemic disease selected from the internal medicine department of Bilawal medical college Hospital Kotri, Sindh, Pakistan for one-year duration from August 2019 to August 2020. Methods: Crossectional study was conducted in the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…Only 22% of patients had optimum diabetic control (HbA1c ≤7%). In other local studies, as many as 35-75% of diabetic patients have poor control based on their HbA1c [13][14].…”
Section: Discussionmentioning
confidence: 95%
“…Only 22% of patients had optimum diabetic control (HbA1c ≤7%). In other local studies, as many as 35-75% of diabetic patients have poor control based on their HbA1c [13][14].…”
Section: Discussionmentioning
confidence: 95%
“…Nomani et al concluded that an elevated risk of ischemic stroke was indicated by an HbA1c higher than 5.6% [ 16 ]. Studies by Oh et al, Ahmed et al, and Raj et al reported that increased HbA1c showed a markedly significant increase in ischemic stroke after adjusting for confounding variables [ 17 - 19 ]. These results align with this present study in which a continuous correlation between the HbA1c values and the risk of ischemic stroke was observed.…”
Section: Discussionmentioning
confidence: 99%